How Will We Pay for Loss and Damage?. Issue 2 (4th May 2017) - Roberts, J. Timmons; Natson, Sujay; Hoffmeister, Victoria; Durand, Alexis; Weikmans, Romain; Gewirtzman, Jonathan; Huq, Saleemul
Abstract: The devotion of a full article in the Paris Agreement to loss and damage was a major breakthrough for the world's most vulnerable nations seeing to gain support for climate impacts beyond what can be adapted to. But how will loss and damage be paid for, and who will pay it? Will ethics be part of this decision? Here we ask what are the possible means of raising predictable and adequate levels of funding to address loss and damage? Utilizing a framework developed by Marco Grasso (2009, 2010), we argue that making the ethical connections between addressing climate impacts and finance mechanisms could significantly enhance their likelihood of being adopted. We briefly review insurance mechanisms and catastrophe bonds, and then move on to six "innovative finance" approaches to funding loss and damage. We utilize six criteria in assessing them: adequacy, predictability, technical feasibility, fairness, and indirect effects, and whether each has a clear link to loss and damage. Several mechanisms for gathering funds emerged as most promising. Three of the six financial mechanisms we reviewed to raise funding involved airline transport: clearly, there is a huge opportunity to tax this sector in one form or another, in recognition of airline emissions' role in creating losses and damages in vulnerable nations from sea level rise, droughts, floods or hurricanes. Funding loss and damage response is a contentious issue that will get only more unwieldy if Parties' conceptions of loss and damage are at odds: a common definition of loss and damage needs to be agreed upon under the UNFCCC. Most immediately, to meet any equity criteria, wealthy countries should do more to support the premiums of those who cannot afford insurance.